Enabling Digital Entrepreneurs - van Welsum, Desirée (World Bank, Washington, DC, 2016)
In the developed world, the emergence of utility-based cloud computing is shifting focus from technical barriers to the business environment challenges facing digital entrepreneurs. This shift reinforces the growing importance of implementing effective policies that foster the best climate for digital service incubation, growth and successful development. However, in many rural areas and developing countries, even basic infrastructure remains a challenge, from the hardware, the network, the content, the ICT eco-system, to the skills on both consumer and business sides.